THE GENDER DIFFERENCES IN THE USAGE OF GRATITUDE AND THE USE OF GRATITUDE EXPRESSIONS IN FUNCTIONAL STYLES OF UZBEK AND ENGLISH LANGUAGES - Mirzaabdullayeva Zumradxon Mahammadjon qizi (Scientific Impulse, 2023)
This article provides a comparison of gender differences and social spheres in expressing gratitude as a speech genre both linguistically and culturally in English and Uzbek languages. The aim of this article is to analyze the main ideas of gratitude expressions in marriage utilized by males and females and how they use them in accordance with their gender, as well as , usage of different gratitude expressions in functional styles of languages.